A Biomimetic Plasmonic Nanoreactor for Reliable Metabolite Detection. Issue 10 (11th March 2020) - Liu, Jiangang; Cai, Chenlei; Wang, Yuning; Liu, Yu; Huang, Lin; Tian, Tongtong; Yao, Yuanyuan; Wei, Jia; Chen, Ruoping; Zhang, Kun; Liu, Baohong; Qian, Kun
Abstract: Reliable monitoring of metabolites in biofluids is critical for diagnosis, treatment, and long‐term management of various diseases. Although widely used, existing enzymatic metabolite assays face challenges in clinical practice primarily due to the susceptibility of enzyme activity to external conditions and the low sensitivity of sensing strategies. Inspired by the micro/nanoscale confined catalytic environment in living cells, the coencapsulation of oxidoreductase and metal nanoparticles within the nanopores of macroporous silica foams to fabricate all‐in‐one bio‐nanoreactors is reported herein for use in surface‐enhanced Raman scattering (SERS)‐based metabolic assays. The enhancement of catalytical activity and stability of enzyme against high temperatures, long‐time storage or proteolytic agents are demonstrated. The nanoreactors recognize and catalyze oxidation of the metabolite, and provide ratiometric SERS response in the presence of the enzymatic by‐product H2 O2, enabling sensitive metabolite quantification in a "sample in and answer out" manner. The nanoreactor makes any oxidoreductase‐responsible metabolite a candidate for quantitative SERS sensing, as shown for glucose and lactate. Glucose levels of patients with bacterial infection are accurately analyzed with only 20 µL of cerebrospinal fluids, indicating the potential application of the nanoreactor in vitro clinical testing. Abstract : Inspired by the spatially confined micro‐/nano‐environment in living cells, a plasmonic bio‐nanoreactor is developed by the coencapsulation of enzyme and surface‐enhanced Raman scattering tags within macroporous silica foams. The nanoreactor shows enhanced biocatalytic activity and stability, and thus the capability of molecular recognition and detection provides an all‐in‐one optical biosensor for reliable in vitro metabolic testing.